Pengaruh Idiosinkratik Shinzo Abe Terhadap Gender Mainstreaming dalam Implementasi Womenomics - Ayu Tiara Karel Bua (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Womenomics is a structural reform step carried out during the second term of Shinzo Abe’s government. This is surprising because Abe, who is considered convervative, dared to initiate policies that contrary to Japanese culture. This research aims to explain how Shinzo Abe's personality and leadership type have influenced womenomics policies and gender mainstreaming. This research uses qualitative research methods and data collection is done through literature study, from books, journal, articles, and websites. The result shows that Abe's idiosyncratic factors and leadership type had a significant influence on womenomics policy making. Family background, life experiences, relationships with political elites playing an important role in shaping Abe's mindset and interest on gender issues. Womenomics is one of the productions of knowledge owned by Shinzo Abe. Then the results of the analysis of Abe's leadership type shows that Abe is a conciliator type who emphasizes cooperation in achieving goals of womenomics through gender mainstreaming. This research suggest the further research on gender in Japan places more emphasis on the legacy of the womenomics policy to the new Prime Minister of Japan, Fumio Kishida.